Assimilation of tracking technology in the supply chain. (June 2018) - Basole, Rahul C.; Nowak, Maciek
Highlights: Use transaction cost economics and institutional theories to understand tracking technology (TT) assimilation. Develop and empirically test a model on global dataset of 535 supply chain executives. Product, supply network, and environmental context have varied impact on assimilation. Provide insights into management of TT in a global and complex business environment. Abstract: While tracking technology has become increasingly accessible, firms still struggle with deploying these technologies into the supply chain. Using the complementary perspectives of transaction cost and institutional theory, we develop an understanding of how supply network, product, and environmental characteristics jointly impact tracking technology assimilation. We empirically test our model on a global dataset of 535 supply chain executives and decision makers. The results suggest that assimilation is frequently initiated by an external stakeholder in a firm's supply chain and that firms must develop strong collaborative ties with their partners in order to take full advantage of this technology.